The Potential Application of Blockchain and Control Tower in Domestic Forwarding Business in Indonesia - Aulia Harumi Baharisa Tya; Suli, Norman Erikson (Indonesian Journal of Business and Entrepreneurship, 2023)
On the global rapid movement, forwarding business face challenges both from the financial and operational aspects within all parties. Advanced growth of information technology through blockchain and control tower model can be a solution which tailored by logistics services provider. The purpose of this study is to analyze the relevant variables that are critical to access the potential adoption of blockchain and control tower scheme for forwarding business activities. Technology Acceptance Model with Partial Least Square used to analyze variables that come from supply chain issues, technologies readiness, cost of technologies, the character of stakeholder, the character of user, perceived ease of use, and perceived usefulness which will influence the intention to use of the blockchain and control tower scheme. Population size of this study coming from 93 respondents of logistics professional in Indonesia with convenience sampling method technique. Based on the 8 hypotheses that developed, the result explained that there are 4 acceptances and 4 rejections of hypotheses. The conclusion explains that Supply Chain Issue have positive impact to Perceived Usefulness, Characters of Stakeholders and Characters of User have positive impact to Perceived Ease of Use, and Cost of Technologies have positive impact to Intention to Use of Blockchain and Control Tower. Keywords: forwarding business, technology acceptance model, blockchain, control tower, partial least square